2018
DOI: 10.3758/s13415-018-0621-5
|View full text |Cite
|
Sign up to set email alerts
|

Ocular signatures of proactive versus reactive cognitive control in young adults

Abstract: During the execution of a cognitive task, the brain maintains contextual information to guide behavior and achieve desired goals. The AX-Continuous Performance Task is used to study proactive versus reactive cognitive control. Young adults tend to behave proactively in standard testing conditions. However, it remains unclear how interindividual variability (e.g., in cognitive and motivational factors) may drive people into more reactive or proactive control under the same task demands. We investigated the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 82 publications
3
9
0
Order By: Relevance
“…Moreover, this measure turned out to be negatively correlated with most behavioral and neurophysiological indices of proactive control, such as A-cue bias, d ’-context, CNV and P3b to B cues. It is in line with previous findings showing that higher RTV is linked with lower proactive responding (Mäki-Marttunen et al, 2018 ) and reduced CNV (Doehnert et al, 2013 ) and indicates that this measure might be considered as another index of proactive control engagement, reflecting processes involved in sustained attention. On the contrary, we did not observe significant correlations between RTV and PBIs.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this measure turned out to be negatively correlated with most behavioral and neurophysiological indices of proactive control, such as A-cue bias, d ’-context, CNV and P3b to B cues. It is in line with previous findings showing that higher RTV is linked with lower proactive responding (Mäki-Marttunen et al, 2018 ) and reduced CNV (Doehnert et al, 2013 ) and indicates that this measure might be considered as another index of proactive control engagement, reflecting processes involved in sustained attention. On the contrary, we did not observe significant correlations between RTV and PBIs.…”
Section: Discussionsupporting
confidence: 92%
“…This means that a participant might see an A cue and set the prepotent intention to report an AX trial in anticipation of an X probe and then inhibit that intention when they see the Y probe. In support of this view, the pupillometry findings of Mäki-Marttunen et al (2018) and the Locus Coeruleus and dlPFC activation found by Mäki-Marttunen et al (2019a, 2019b) support the involvement of inhibitory control in the AX-CPT. Furthermore, the especially long response times on AY trials might suggest that participants sometimes override their intention to report an AX pair when they see the Y probe (Mäki-Marttunen et al, 2018;Mäki-Marttunen et al, 2019b).…”
Section: Inhibition Of Prepotent Intentionsmentioning
confidence: 54%
“…Recent physiological data and reaction time data suggest that there might be an additional control mechanism influencing people's responses in the AX-CPT, namely the inhibition of prepotent responses (Mäki-Marttunen et al, 2018;Mäki-Marttunen et al, 2019b). This means that a participant might see an A cue and set the prepotent intention to report an AX trial in anticipation of an X probe and then inhibit that intention when they see the Y probe.…”
Section: Inhibition Of Prepotent Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, participants would show more reactive cognitive control after HF-rTMS over the right DLPFC ( Vanderhasselt et al., 2009 ). Previous studies have demonstrated that changes in pupil size can be used to investigate the allocation of cognitive resources or mental effort during the AX-CPT ( Chiew and Braver, 2013 , 2014 ; Mäki-Marttunen et al., 2018 ). Chiew and Braver (2013 ) showed that an increase in proactive control provokes a sustained increase in pupil size measured in the period immediately before the cue is presented, reflecting sustained resource allocation during the task.…”
Section: Introductionmentioning
confidence: 99%